Effect of graphene on the interfacial and mechanical properties of hybrid glass/Kevlar fiber metal laminates. Issue 2 (June 2022) - Hosseini Abbandanak, S Navid; Abdollahi Azghan, Mehdi; Zamani, Amin; Fallahnejad, Mehrdad; Eslami-Farsani, Reza; Siadati, Hossein
The remarkable resurgence of fiber metal laminates (FMLs) is certainly attributed to the hybrid properties inherent to light metals and fibers reinforced polymer (FRP). There are few reports on the role of nano-size reinforcements in these composites. In this study, the effect of graphene nanoplatelets (GNPs) on the flexural and Charpy impact properties of FMLs of aluminum (Al) 2024 reinforced with hybrid glass/Kevlar fibers-epoxy was investigated. Different wt.% of GNPs (0.0, 0.1, 0.25 and 0.5) and hand lay-up method were used to fabricate nano-FMLs followed by evaluating them in three-point bend and Charpy impact tests. Before making the FMLs, the surfaces of Al sheets were modified to generate surface pores/nano-pores in order to improve the interfacial bonding within the FMLs layers. The FMLs containing 0.1 wt.% GNPs exhibited 10%, 9% and 11% improvement in flexural strength and modulus and impact strength, respectively, compared to the FMLs containing 0.0 wt.% GNPs. Increase of the GNPs to 0.25 wt.% caused a reduction of the flexural strength and modulus and impact strength values; 13.7%, 3% and 25.5% compared to the samples without GNPs. Also increase of the GNPs to 0.5 wt.% decreased these properties to 31.3%, 8.8% and 29.5%. Scanning electron microscopy (SEM) observations of their fracture surfaces showed better adhesion at both polymer/fibers (within the FRP) and Al/FRP interfaces. However, at higher wt.% of GNPs, the FMLs became weaker and more brittle. Agglomerated GNPs at the Al/FRP interface penetrated/filled the surface pores/nano-pores on the Al surfaces. Therefore prevent the polymer penetration in pores, resulting in weak interfacial bond and thus overall weaker and less ductile FMLs. As a result, the Charpy impact values for the 0.25 and 0.5 wt.% GNPs samples were respectively 33 and 37 percent smaller than that for the 0.1 wt.% GNPs sample.